Prison Visitation and Concerns about Reentry: Variations in Frequency and Quality of Visits are Associated with Reentry Concerns among People Incarcerated in Prison - Baker, Thomas (International journal of offender therapy and comparative criminology, 2022)
Prior studies suggest that visitation may have an impact on successful reentry. At the same time, the impact of visitation on incarcerated people’s concerns about reentry has received little empirical attention. Understanding how factors such as visitation affect concerns about reentry can provide correctional officials with policy directions on how to reduce strains and enhance successful reintegration. Further, while some studies have evaluated frequency of visitation far fewer have examined the impact of quality of visitation. Using a sample of males and females incarcerated in five correctional facilities (n = 3,084), this study examines how frequency and quality of visitation impact incarcerated people’s concerns about employment, housing, debt, and recidivism upon reentry. Findings suggest that more visits reduce concerns, while negative visits increase concerns about reentry.